2002
DOI: 10.1002/1521-3773(20020703)41:13<2348::aid-anie2348>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Monodentate Chiral Spiro Phosphoramidites: Efficient Ligands for Rhodium-Catalyzed Enantioselective Hydrogenation of Enamides

Abstract: Optically active a-arylalkylamines are an important class of compounds that are widely used in organic and pharmaceutical synthesis, and much effort has been made to develop efficient asymmetric synthetic methods for them. [1] Asymmetric catalytic hydrogenation of enamides, initiated by Kagan et al., [2] provides a direct and convenient route to chiral amine derivatives. However, many well-known chiral diphosphane ligands, such as DIOP, BINAP, and CHIRA-PHOS, which are extremely successful in the asymmetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(85 citation statements)
references
References 25 publications
1
82
0
2
Order By: Relevance
“…29 Here, it was found that the % ee remained roughly constant at 89 ¡ 2%, in the hydrogenation of 1a at 383 K and 100 bar total, by varying the initial hydrogen pressure from 2 to 20 bar. These results complement those obtained using conventional organic solvents employing rhodium/ MonoPhos 24,25,28 and rhodium/MonoPhos-based 30 catalysts that have illustrated that the hydrogen pressure has no effect on enantioselectivity, and suggest that the mechanism of rhodium/MonoPhos catalysis is the same in sc fluids as in liquid solvents. A study by Poliakoff et al 31 showed that the critical parameters of CO 2 were reduced during the hydrogenation of propane as the ratios of reagents to products changed.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…29 Here, it was found that the % ee remained roughly constant at 89 ¡ 2%, in the hydrogenation of 1a at 383 K and 100 bar total, by varying the initial hydrogen pressure from 2 to 20 bar. These results complement those obtained using conventional organic solvents employing rhodium/ MonoPhos 24,25,28 and rhodium/MonoPhos-based 30 catalysts that have illustrated that the hydrogen pressure has no effect on enantioselectivity, and suggest that the mechanism of rhodium/MonoPhos catalysis is the same in sc fluids as in liquid solvents. A study by Poliakoff et al 31 showed that the critical parameters of CO 2 were reduced during the hydrogenation of propane as the ratios of reagents to products changed.…”
Section: Resultssupporting
confidence: 84%
“…34 The reagent amounts for the constant mole fraction asymmetric hydrogenation studies were 8. 25 In a typical catalytic evaluation, small quantities of reagents were introduced into the cell by dissolving the solid in an appropriate organic solvent and transferring the solution using a Gilson pipette. The air-sensitive catalyst was dissolved in dried and degassed solvents and transferred into the catalystloading chamber in a glove box.…”
Section: Methodsmentioning
confidence: 99%
“…1). These ligands have found a wide range of applications in metalcatalyzed asymmetric transformations such as hydrogenation (5,(8)(9)(10)), 1,4-additions of dialkylzinc (11,12) and boronic acids (13) to enones, hydrovinylation (14), hydrosilylation (15), intramolecular Heck reaction (16), hydroformylation (17), allylic alkylation (18,19), amination (20), and etherification (21).…”
mentioning
confidence: 99%
“…The first example of enantioselective hydrogenation of enamides with monodentate phosphorus ligands for the synthesis of chiral amines was reported by Zhou and coworkers in 2002 [15]. By using the rhodium complex bearing a chiral spirobiindane phosphoramidite ligand SIPHOS, a variety of enamides can be hydrogenated to produce the corresponding amines with excellent enantioselectivities.…”
Section: Asymmetric Hydrogenation Of Enamidesmentioning
confidence: 99%